Implementation of an active damping system to reduce harmonic vibrations in a 3DOF model - Carlos Moutinho (2005)
This paper describes the work for a real implementation of an active damping system to reduce harmonic vibrations in a plane frame physical model with 3 degrees-of-freedom. For this purpose, it is suggested the use of an active mass damper commanded by a derivate controller which has the effect of increasing the modal damping coefficients in correspondence with a specific gain value. This control gain, as well as the system stability, was evaluated using the root-locus technique. The efficiency of the proposed control system to achieve pre-defined damping ratios was verified experimentally, by analyzing the free decay responses of the system after being excited at resonant frequencies.